Влияние электронного облучения на спектр фотолюминесценции пористого кремния - Алиев, Б.А. (Изд-во КарГУ, 2010)
Мақалада 2 МэВ энергиялы жəне 1014–1017 см-2 дозалы электрондық сəулеленудің кеуек кремнийдің ИҚ-спектрлеріне жəне фотолюминесценция (ФЛ) спектріне əсері қарастырылған. Сəулелендіруге кеуек кремнийдің жаңа жəне бір жыл бұрын дайындалған үлгілері ұшырады. Нəтижесінде жаңа дайындалған үлгілер тез бұзылуға бейім екені байқалды. In present work explored influence electronic irradiation with energy 2 MeV and dose 1014–1017 sm–2 on spectrum photoluminescence (FL) and IR-spectrums porous silicon (PS). The irradiation were subjected to as the prepared sample PS, so and sample, prepared year back. It is noted that most powerfully the photoluminescence degrades sample moreover, than fine film PC that more degradates. Increase the dose more than 1015 sm–2 bring about reduction of the intensities FL and under D = 1016 sm–2 her (its) extinguish in 4 times. Radiacia-steadfast turned out to be the sample of long keeping from thick layers PC, under D = 1016 sm–2 FL decreased only on 20 %.
Influence of the electronic irradiation on spectrum photoluminescence porous silicon